Lung consolidation as a rare presentation of lymphoplasmacytic lymphoma with extramedullary Waldenström's macroglobulinemia - Omar Abdulfattah; Ebad Ur Rahman; Bikash Bhattarai; Sumit Dahal; Zainab Alnafoosi; David Trauber; Danilo Enriquez; Frances Schmidt (Greater Baltimore Medical Center, 2018)
Objectives: Lymphoplasmacytic lymphoma (LPL) is a mature B cell lymphoma that usually involves the bone marrow, spleen and lymph nodes. Extramedullary involvement, including the lung, is rarely reported. Case description: A 73-year-old female initially presented to our hospital complaining of productive cough of white-colour sputum for three weeks duration. She reported unintentional weight loss of ten pounds over the last five months. There was no history of haemoptysis, fever, night sweats, chills, recent infections or hospitalization. Chest imaging showed right lower lobe consolidation, small right pleural effusion. She was treated with oral antibiotic for pneumonia. After two months, a follow up chest imaging revealed persistent right lower lobe consolidation. Therefore, she was worked up for the possibility of malignancy. Bronchoscopy showed polypoid nodularities surrounded by black discoloured mucosa in the sub-segmental bronchi of the right lower lobe, and biopsy specimen revealed atypical B cell lymphocytic infiltrate. Polymerase chain reaction confirmed a clonal B-cell gene rearrangement supportive for a low-grade B-cell Lymphoma. Subsequently; serum immunofixation showed IgM of 1491 mg/dL (normal range 26-217 mg/dl) with normal levels of IgG and IgA. Urine contained free kappa light chains. Cytology with immunophenotyping of pleural fluid revealed lymphoplasmacytic lymphocytes. This combination of lab and bronchoscopy findings established the diagnosis of extramedullary Waldenström's macroglobulinemia. Conclusion: Waldenström's macroglobulinemia, a manifestation of LPL, is associated with an IgM monoclonal gammopathy in the blood. Extramedullary involvement including the lung is rarely seen in LPL. Physicians need to be aware of this rare presentation.